2020
DOI: 10.1002/wmon.1052
|View full text |Cite
|
Sign up to set email alerts
|

The Catastrophic Decline of Tortoises at a Fenced Natural Area

Abstract: Agassiz's desert tortoise (Gopherus agassizii), a threatened species of the southwestern United States, has severely declined to the point where 76% of populations in critical habitat (Tortoise Conservation Areas) are below viability. The potential for rapid recovery of wild populations is low because females require 12-20 years to reach reproductive maturity and produce few eggs annually. We report on a 34-year mark-recapture study of tortoises initiated in 1979 at the Desert Tortoise Research Natural Area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 179 publications
(280 reference statements)
0
23
0
Order By: Relevance
“…Ongoing PCR based surveys to provide insight into the prevalence, incidence, and clinical outcomes of apparently asymptomatic individuals following this mortality event are required. Opportunistic sample collection associated with population monitoring surveys presents a cost-effective option for infectious disease detection and monitoring and could be considered for other reptile species ( 46 , 47 ).…”
Section: Hosts and Geographic Distributionmentioning
confidence: 99%
“…Ongoing PCR based surveys to provide insight into the prevalence, incidence, and clinical outcomes of apparently asymptomatic individuals following this mortality event are required. Opportunistic sample collection associated with population monitoring surveys presents a cost-effective option for infectious disease detection and monitoring and could be considered for other reptile species ( 46 , 47 ).…”
Section: Hosts and Geographic Distributionmentioning
confidence: 99%
“…Trend estimates also can be influenced by the length of the time series, timing of year zero relative to natural population fluctuations, and the extent to which areas surveyed reflect the larger population of interest (Fournier et al, 2019;White, 2019). The trend estimates we report are less likely to reflect site-selection bias than previous estimates that were derived from plots established purposefully in areas of high-quality habitat with sufficient numbers of individuals to estimate density based on capture-recapture methods (USFWS, 2011; e.g., Berry & Medica, 1995;Berry et al, 2020).…”
Section: Population Trendsmentioning
confidence: 72%
“…Previous studies have identified environmental features associated with the presence of tortoises throughout their geographic range (Nussear et al, 2009), but less effort has been directed toward identifying environmental features that explain variation in density. Although other studies have provided local estimates of density (e.g., Berry et al, 2020; Mitchell et al, 2021), data limitations and computational hurdles have made it challenging to generate rigorous estimates that are comparable across the species' range. By leveraging data from the range‐wide survey effort led by USFWS and using recent modeling and software advancements, we were able to estimate local densities and regional trends across much of the range of the Mojave desert tortoise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few remained alive on 3 of the 4 plots after 10.5 years. Measured in terms of a wild population of chelonians, the deaths of >50% of adults over 10 years would be treated as a catastrophe (Keevil et al 2018, Berry et al 2020). This and many other species of tortoises and turtles are susceptible to such events because of their life-history traits (Brooks et al 1991;Congdon et al 1993Congdon et al , 1994Garber and Burger 1995).…”
Section: Survivalmentioning
confidence: 99%